Genetic variation of Balmea stormiae (Rubiaceae) in west-central Mexico - Mejía-Jiménez, Dulce Karina; Montero Castro, Juan Carlos; González-Rodríguez, Antonio; Lara-Cabrera, Sabina Irene; Ruiz-Sánchez, Eduardo; Mendoza-Cuenca, Luis Felipe (Instituto de Ecología, A.C., 2022)
Background and Aims: Individuals of Balmea stormiae (Rubiaceae) are trees or hemiepiphytic shrubs that inhabit pine-oak forests on rock outcrops in disjunct populations of Central America and Mexico. The species is considered endangered and especially the populations of Michoacán have been reported as exposed to strong anthropogenic pressures. For this reason, in this study the genetic diversity of four populations of Michoacán was estimated, contrasting this information with that obtained from one population of Jalisco, both regions located in west-central Mexico.Methods: Samples were collected in five populations in the western region of the Trans-Mexican Volcanic Belt. The chloroplast rps16 intron, the external transcribed spacer of ribosomal DNA (ETS) and seven Inter-Simple Sequence Repeats of nuclear DNA (ISSR) were used to assess genetic diversity.Key results: Molecular markers revealed high genetic differentiation between the populations from Jalisco and Michoacán, attributed to the low connectivity amongst them, probably due to the low long distance dispersal capacity of seeds and pollen. Moderate genetic flow and demographic expansion were detected for populations in Michoacán. The degree of genetic diversity in Michoacán populations are consistent with the age of lava flows, whereby Arocutín and Zacapu are the most diverse populations located on the oldest lava flows.Conclusions: Results could be explained by the relatively recent origin, resulting from Holocene volcanic activity, of the environments in which the species inhabits, coupled with the recurring disturbance related to large pre-Hispanic settlements.